The Final Inch: What Pop-Up COVID Testing Tells Us about Community Engagement. Issue 1 (October 2022) - Della Vella, Dante; Rayo, Michael F.
The COVID-19 pandemic has highlighted the need for increased and more dynamic access to healthcare resources. It has also revealed a novel complication to the effective delivery of health resources to communities, which we call the final inch problem. In our recent COVID-19 pop-up testing work with Columbus Public Health and the Ohio National Guard, we have observed that, even when a healthcare-related service is transported directly to community members, it is not a given that they will use that service. We argue that crossing this final inch will require us to reframe public health initiatives through the lens of joint activity: a partnership between healthcare institutions and the public. Our work focuses on three questions. How do we engage with the public and foster common groun d between people and our healthcare providers? As part of this, how can we work with the community to determine where to dynamically direct our resources on a given day? Finally, when we show up at the "right" place, will the community join us? Our recent work creating and deploying the Flexible Algorithmic, Adaptive Surveillance Testing (FAAST) has generated promising insights to answer these questions. Throughout our initial tests, we observed a continuous increase in community participation as well as increased positivity through multiple iterations of the program. We consistently overrepresented traditionally underserved minority groups in all testing locations as well. Insights for convincing communities to participate in pop-up testing may yield repeatable, generalizable strategies by which public health officials and healthcare providers may cross the final inch. Through establishing and nurturing reliable community relationships, public health institutions working in partnership with their constituent communities can proactively monitor the health of their communities, thereby facilitating a more resilient response to emerging threats.